Amplifying the Red-Emission of Upconverting Nanoparticles for Biocompatible Clinically Used Prodrug-Induced Photodynamic Therapy - Punjabi, Amol (American Chemical Society, 2014)
[Image: see text] A class of biocompatible upconverting nanoparticles (UCNPs) with largely amplified red-emissions was developed. The optimal UCNP shows a high absolute upconversion quantum yield of 3.2% in red-emission, which is 15-fold stronger than the known optimal β-phase core/shell UCNPs. When conjugated to aminolevulinic acid, a clinically used photodynamic therapy (PDT) prodrug, significant PDT effect in tumor was demonstrated in a deep-tissue (>1.2 cm) setting in vivo at a biocompatible laser power density. Furthermore, we show that our UCNP–PDT system with NIR irradiation outperforms clinically used red light irradiation in a deep tumor setting in vivo. This study marks a major step forward in photodynamic therapy utilizing UCNPs to effectively access deep-set tumors. It also provides an opportunity for the wide application of upconverting red radiation in photonics and biophotonics.